Sociodemographic, clinical and survival profile of adult metastatic patients - Vanessa Kelly Cardoso Estumano; Taís dos Passos Sagica; Gisela Pereira Xavier Albuquerque; Marta Solange Camarinha Ramos Costa; Odenilce Vieira Pereira; Edjane Marcia Linhares Melo; Sílvio Éder Dias da Silva; Aline Maria Pereira Cruz Ramos (Universidade Federal do Rio Grande do Sul, 2023)
ABSTRACT Objective: To characterize the sociodemographic, clinical and survival profile of adult metastatic patients. Method: Retrospective cross-sectional study, with secondary data from an oncology care unit, analyzed using logistic regression, Chi-Square test and Fisher's exact test, Kaplan-Meier and Log-Rank tests. Results: From the 678 patients, male gender, mean age 59.54 years old and low education level prevailed. The mean time between diagnosis and initiation of treatment was 89.50 days (± 58.87). Increased risk of primary cancer in the digestive tract (OR 1.42). Prevalence of adenocarcinoma (OR 1.53) and metastasis to bone (OR 2.59), lymph nodes (OR 1.75), liver and peritoneum (OR 1.42). The mean overall survival was 4.16 months and a median of 3.0 months. Conclusion: The main primary site was the digestive system, and the identification of metastases was predominantly unifocal liver in both genders. Overall patient survival was reduced by cancer progression.